Not Afraid of Spells and Curses - Mitić, Kristina R. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The similarity between the South Slavic customs of rainmaking and the common Slavic agrarian customs of the spring-summer cycle is high. Some special songs and games were created and developed, which were sung and played at youth meetings during beautiful spring afternoons and evenings (somewhere at night too, around nightfires in March). There were many songs and they were sung only during the Holy Fast. When winter turned to spring, songs were sung on a ”ranilo”, from March 1 to April 7, but earlier too, after Christmas. These songs intertwine with love and family, as many ritual songs do. The basis of the text is ”fertility magic”. The songs on a ”ranilo” were sung by girls and young women, rarely men. The songs of the Palm Sunday were sung by girls dancing at dawn after Lazarus Saturday, usually in a churchyard or at an elevated place in a settlement.
Keywords: ”ranilo”; ”ráne”; fertility magic; songs